2015
DOI: 10.1002/ceat.201500233
|View full text |Cite
|
Sign up to set email alerts
|

H2S Reactive Absorption from Off‐Gas in a Spray Column: Insights from Experiments and Modeling

Abstract: H 2 S removal from an off-gas stream was performed in a spray column by H 2 S reactive absorption into a NaOH solution. The individual and interactive effects of three independent operating variables on the percentage of absorbed H 2 S were investigated: the initial pH of the scrubbing solution, the initial scrubbing solution temperature, and the volumetric liquid-to-gas ratio. The optimum operating variables were determined by response surface methodology (RSM) attaining a percentage of absorbed H 2 S of 98.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Table 6 shows that the ANN model with larger R 2 and smaller MSE and AAD values is superior to the RSM model in predicting Y. Additionally, the ANN model is not limited to number of experiments and it is applicable to complicated non-linear processes [21,28].…”
Section: Comparison Between Results Of Rsm and Ann Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 6 shows that the ANN model with larger R 2 and smaller MSE and AAD values is superior to the RSM model in predicting Y. Additionally, the ANN model is not limited to number of experiments and it is applicable to complicated non-linear processes [21,28].…”
Section: Comparison Between Results Of Rsm and Ann Modelsmentioning
confidence: 99%
“…It consists of an input layer, one or more hidden layers and an output layer. Each layer involves processing units called neurons which operate independently of others [27,28]. In the current study, a MLFF network was applied with the architecture as shown in Figure 2: an input layer included three operating conditions as input neurons, an output layer with one neuron, and one hidden layer which its neurons can change to gain the best ANN performance.…”
Section: Ann Model Descriptionmentioning
confidence: 99%
“…ANNs are inspired by biological nervous systems such as brain and consist of elements that receive inputs and generate a single output, where the output is a function of the inputs. ANN has large numbers of computational units connected in a massively parallel structure and do not require a mathematical formulation or physical relationships of the handled problem [20,21]. This property is a significant advantage of the flexible ANN model to predict complicated systems.…”
Section: Artificial Neural Network (Ann) Modelmentioning
confidence: 99%
“…For the latter purpose, the application of reliable and adequate process models is widespread 11. Useful models can be found in the literature for many chemical air scrubber applications, such as the desulfurization process 12–14, the absorption of odorous compounds 15, 16, and the absorption of ammonia in water using different scrubbing systems 17–22. However, none of these models consider the pollutant removal efficiency simultaneously with temperature and water evaporation, which is essential to assess the interaction between the scrubber performance, the temperature dynamics, and the water consumption.…”
Section: Introductionmentioning
confidence: 99%